Effect of Spirituality-Based Palliative Care on Pain, Nausea, Vomiting, and the Quality of Life in Women with Colon Cancer: A Clinical Trial in Southern Iran - Sabet, Parisa (Journal of religion and health, 2023)
This randomized controlled clinical trial aimed to examine the effect of spirituality-based palliative care on pain, nausea, vomiting, and the quality of life in 80 Iranian colon cancer inpatients from January to June 2020 in southern Iran. Patients were randomly assigned to an intervention group and a control group. The intervention group took part in four 120-min sessions while the control group received standard care. Pain, nausea, vomiting, and quality of life were assessed before the intervention and one month after the intervention. Data were analyzed using paired t-test and independent t-test. Between-groups differences analysis showed a significant difference in the quality of life scores, pain score, as well as nausea and vomiting scores following the one-month intervention. In conclusion, this group spirituality-based palliative care intervention might be beneficial in improving quality of life and reducing symptoms.